Comment On: Association of HOTAIR rs1899663 G>T Polymorphism with Colorectal Cancer in the Turkish Population: A Case–Control Study - Juan Pablo Meza-Espinoza,; Evelia Leal-Ugarte,; Verónica Judith Picos-Cárdenas, (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Meza-Espinoza JP, Leal-Ugarte E, Picos-Cárdenas VJ. Comment on: Association of HOTAIR rs1899663 G>T polymorphism with colorectal cancer in the Turkish population: A case–control study. Turk J Gastroenterol. 2023;34(7):779.